Comparison of Common Methodologies for the Determination of Knee Flexor Muscle Strength - Dan I Ogborn; Alix Bellemare; Brittany Bruinooge; Holly Brown; Sheila McRae; Jeff Leiter (North American Sports Medicine Institute, 2021)
# Background Knee flexion strength may hold important clinical implications for the determination of injury risk and readiness to return to sport following injury and orthopedic surgery. A wide array of testing methodologies and positioning options are available that require validation prior to clinical integration. The purpose of this study was to 1) investigate the validity and test-retest reliability of isometric knee flexion strength measured by a fixed handheld dynamometer (HHD) apparatus compared to a Biodex Dynamometer (BD), 2) determine the impact of body position (seated versus supine) and foot position (plantar- vs dorsiflexed) on knee flexion peak torque and 3) establish the validity and test-retest reliability of the NordBord Hamstring Dynamometer. # Study Design Validity and reliability study, test-retest design. # Methods Forty-four healthy participants (aged 27 ± 4.8 years) were assessed by two raters over two testing sessions separated by three to seven days. Maximal isometric knee flexion in the seated and supine position at 90^o^ knee flexion was measured with both a BD and an externally fixed HHD with the foot held in maximal dorsiflexion or in plantar flexion. The validity and test-retest reliability of eccentric knee flexor strength on the NordBord hamstring dynamometer was assessed and compared with isometric strength on the BD. # Results Level of agreement between HHD and BD torque demonstrated low bias (bias -0.33 Nm, SD of bias 13.5 Nm; 95% LOA 26.13 Nm, -26.79 Nm). Interrater reliability of the HHD was high, varying slightly with body position (ICC range 0.9-0.97, n=44). Isometric knee flexion torque was higher in the seated versus supine position and with the foot dorsiflexed versus plantarflexed. Eccentric knee flexion torque had a high degree of correlation with isometric knee flexion torque as measured via the BD (r=0.61-0.86). The NordBord had high test-retest reliability (0.993 (95%CI 0.983-0.997, n=19) for eccentric knee flexor strength, with an MDC~95~ of 26.88 N and 28.76 N for the left and right limbs respectively. # Conclusion Common measures of maximal isometric knee flexion display high levels of correlation and test-retest reliability. However, values obtained by an externally fixed HHD are not interchangeable with values obtained via the BD. Foot and body position should be considered and controlled during testing. # Level of Evidence 2b